PENGARUH VARIABEL MAKROEKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) - Nency Megawati; M. Noor Salim (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
This study aims to analyze the macroeconomic variables that affect the Composite Stock Price Index (CSPI). Data analysis using multiple linear regression analysis with 32 stock samples during the period of Quarter I 2009 to Quarter IV 2016. The results showed that the Exchange Rate and Dow Jones Index had a positive and significant effect on the Composite Stock Price Index (CSPI), Inflation and the BI Rate had no significant effect on the Composite Stock Price Index (CSPI).